2024
DOI: 10.3390/electronics13071178
|View full text |Cite
|
Sign up to set email alerts
|

An Open-Source Face-Aware Capture System

Md Abdul Baset Sarker,
S. M. Safayet Hossain,
Naveenkumar G. Venkataswamy
et al.

Abstract: Poor-quality facial images pose challenges in biometric authentication, especially in passport photo acquisition and recognition. This study proposes a novel and open-source solution to address these issues by introducing a real-time facial image quality analysis utilizing computer vision technology on a low-power single-board computer. We present an open-source complete hardware solution that consists of a Jetson processor, a 16 MP autofocus RGB camera, a custom enclosure, and a touch sensor LCD for user inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The system detects the face using dlib and detects facial landmark points using a 68 landmark points detector [17,18]. After detecting the landmark points, geometric and photographic checks are performed, as denoted in [3]. Under the category of geometric tests, parameters such as eye distance, vertical and horizontal position, head image width, and height ratios are measured to meet specified criteria.…”
Section: Softwarementioning
confidence: 99%
See 2 more Smart Citations
“…The system detects the face using dlib and detects facial landmark points using a 68 landmark points detector [17,18]. After detecting the landmark points, geometric and photographic checks are performed, as denoted in [3]. Under the category of geometric tests, parameters such as eye distance, vertical and horizontal position, head image width, and height ratios are measured to meet specified criteria.…”
Section: Softwarementioning
confidence: 99%
“…In a previous project focused on adult passport photo capture, we implemented 68 landmark points and checked face image quality [3]. During this development, we found that automatic camera adjustment with face position would significantly aid in collecting data from children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the widespread use of camera-based solutions across different systems [12,13], we have adopted this approach in our design. For projects focused on image analysis, single-board computers like the Jetson Nano [14][15][16][17][18], Google Coral [19,20], and Raspberry Pi [21][22][23] are favored for their compact size and low power consumption. To optimize our system, we have used the Google Coral Dev Board Mini to run image processing and control peripherals because of its smaller size and inclusion of a Tensor Processing Unit (TPU) for faster processing of deep learning models.…”
Section: Introductionmentioning
confidence: 99%